PERBANDINGAN KADAR HEMOGLOBIN, GLUKOSA DARAH, DAN LEUKOSIT SEBELUM DAN SESUDAH HEMODIALISA PADA PASIEN GAGAL GINJAL KRONIS KOMORBID DAN NON KOMORBID DIABETES MELLITUS DI RSPC - Risma Adzkia Putri; Ira Pangesti; Meka Faizal Farabi (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Chronic Kidney Disease (CKD) is an impairment of the glomerular organ function of the kidneys. The process of blood purification by collecting waste is called hemodialysis. The prevalence of CKD increased from 1990 to 2017 globally by 21.3% and the mortality rate increased by 41.5%. The purpose of this study was to compare hemoglobin, leukocyte, and blood glucose levels before and after hemodialysis in patients with and without comorbid Diabetes Mellitus (DM) at Pertamina Cilacap Hospital (RSPC). The method used was cross sectional using univariate and bivariate analysis with JASP program. The results showed that in CKD patients without DM, hemoglobin levels were significantly different (p<0.05) after hemodialysis. While leukocyte and glucose levels had no significant difference (p>0.05). In CKD patients with DM, there is a significant difference in hemoglobin levels (p<0.05) after hemodialysis. In addition, there is a significant difference in glucose levels (p<0.05) after hemodialysis. Meanwhile, there was no significant difference in leukocyte levels (p>0.05). Comparison of pre and post hemodialysis between CKD without DM and CKD with DM there is a significant difference (p<0.05) in hemoglobin and blood glucose levels but there is no significant difference (p>0.05) in leukocyte levels.